Social Inclusion in Poland : Key Challenges and Opportunities for Support - Owen, Daniel; Morgandi, Matteo; Malarski, Ryszard; Swinkels, Rob; Morrica, Valerie (World Bank, Washington, DC, 2016)
The objective of this policy note is to develop a set of actionable recommendations for tackling poverty and social exclusion in Poland based on evidence. In recent years, the World Bank has deepened its engagement in Poland around issues of social inclusion, through work on effective labor market and activation policies, social assistance benefits, and investment financing for local social inclusion initiatives. This note purports to integrate the outputs of these activities and complement them with insights from the new analytical work to develop recommendations for the government of Poland for program choices to enhance the impact of inclusion programs and employment services. This policy note is structured as follows: (i) introduction; (ii) section two provides a definition of social inclusion and describes the country context by key trends and key groups at risk of social exclusion; (iii) section three provides an overview of the institutional set-up to deliver policies for social inclusion at the national and local level and presents an assessment of the achievements and challenges of key policy instruments (employment services, social benefits, social services, and the work of civil society); (iv) section four focuses on two recent operational experiences of relevance to a future operation: an assessment of the execution of the European Social Fund in Poland against the social and labor agendas and a presentation of the learning generated through the social inclusion component of the World Bank Post Accession Rural Support Project; and (v) section five illustrates areas for potential intervention at the policy and operational level in Poland. Recognizing that social inclusion outcomes are the result of a complex set of factors on the demand and supply side,recommendations include macro-level institutional reforms and changes to local service delivery for inclusion of vulnerable groups, mobilization and capacity support, strategies for local employment generation, and monitoring and accountability support.